Search for double β-decays of 96Ru and 104Ru with high purity Ge γ-spectrometry - P. Belli; R. Bernabei; F. Cappella; R. Cerulli; F. A. Danevich; S. d'Angelo; A. Incicchitti; M. Laubenstein; O. G. Polischuk; D. Prosperi; V. I. Tretyak (Ядерна фізика та енергетика)
Experiment to search for double β decay of 96Ru and 104Ru is in progress in the underground Gran Sasso National Laboratories of the INFN (Italy) with the help of ultra-low background high purity (HP) Ge γ spectrometry. After 2162 h of data taking with 473 g ruthenium sample in low-background set-ups with HP Ge detectors, new improved limits on 2β processes in 96Ru and 104Ru have been established on the level of 1018–1019 yr.